Exploring the Impact of Live Streaming on Consumer Purchase Intention: An Analysis Using the Theory of Planned Behavior - Yen Yen, Ong; Nasuredin, Juzaimi; Ma’rof, Rabiatul Adawiyah (JBS Nexus, 2024)
With the rise of live-streaming as a direct marketing tool, many individual sellers have adopted this medium to engage consumers and drive online sales. The shift towards online shopping, accelerated by the COVID-19 pandemic, has fueled consumer interest in new digital purchasing behaviors, including e-commerce live streaming. While prior studies have explored consumers' purchasing behavior in the context of online shopping, there remains a gap in understanding the specific factors influencing purchase intentions through live streaming. This study examines the relationship between live streaming and consumers' purchase intention, guided by the Theory of Planned Behavior (TPB) model. Using a quantitative approach, data were collected via survey questionnaires distributed to 384 consumers in Perak, Malaysia, through Google Forms, with 286 responses successfully analyzed using the Statistical Package for the Social Sciences (SPSS) version 27. Findings from Spearman’s rho correlation test indicate a positive and significant relationship between the independent variables—streamer credibility, media richness, and interactivity—and the dependent variable, consumer purchase intention. This study offers valuable insights for online marketers and researchers seeking to understand how live streaming can influence consumer buying decisions, providing a foundation for enhancing e-commerce strategies and future academic inquiry.